A Narrative Review : Hubungan Antara Tingkat Stress Akademik dan Konsumsi Makanan/Minuman Manis pada Mahasiswa - Jasmine Esfandiari Secondiva Siswadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Academic stress is a common problem among students, especially in final college students. Academic stress refers to feeling of pressure, both physically and emotionally, with a problem about academic. Objective: This research aims to analyze the relationship between academic stress level and consumption of sweet foods or drinks in college students. Method: This research used a literature review based on five articles retrieved from Google Scholar, Pubmed, and ScienceDirect, articles used were published between 2021 and 2025. Result: Based on the result of five articles, there is a relationship between stress and consumption of sweet foods or drinks. The research identified consistent patterns that stress often leads to increased consumption of high sugar as a coping mechanism. When stressed, someone tends to eat sweet foods or drinks, because they have a sense of calm and are able to restore energy quickly. Conclusion: There has been much research conducted related to the relationship between stress and consumption of sweet foods or drinks. Future research should prioritize interventional studies to develop strategies that support self-regulation, physical activity, and better diet quality for overall college student well-being.